The accidental library manager - Gordon, Rachel Singer (Information Today, 2005)
"Most librarians enter the field intending to focus on a particular specialty, but eventually need to take on certain supervisory or managerial responsibilities in order to move forward. In The Accidental Library Manager, author Rachel Singer Gordon provides support and background for new managers, aspiring managers, and those who find themselves in unexpected management roles. Gordon fills in the gaps left by brief and overly theoretical library school coursework, showing library managers how to be more effective in their positions and how to think about their work in terms of the goals of their larger institutions. Included are insights from working library managers at different levels and in various types of libraries, addressing a wide range of management issues and situations. Not to be missed: comments from library staff about the qualities they appreciate-and the styles and attitudes they find counterproductive-in their own bosses. This readable and reassuring guide is a must for any librarian who wishes to succeed in a management position."--